2021
DOI: 10.3390/curroncol28050298
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Spectral Mammography Assessment of Patients Treated with Neoadjuvant Chemotherapy for Breast Cancer

Abstract: Background: Evaluating the tumor response to neoadjuvant chemotherapy is key to planning further therapy of breast cancer. Our study aimed to evaluate the effectiveness of low-energy and subtraction contrast-enhanced spectral mammography (CESM) images in the detection of complete response (CR) for neoadjuvant chemotherapy (NAC) in breast cancer. Methods: A total of 63 female patients were qualified for our retrospective analysis. Low-energy and subtraction CESM images just before the beginning of NAC and as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
3
7
0
Order By: Relevance
“…We found a high degree of correlation between maximum tumor diameter after NAC by CESM and histopathology similar to a previously published study [2]. A study by Lotti and colleagues [31] reported that CESM showed a better correlation with histopathology compared to MRI with Lin's coefficient of 0.81 and 0.59 for CESM and contrast-enhanced MRI, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found a high degree of correlation between maximum tumor diameter after NAC by CESM and histopathology similar to a previously published study [2]. A study by Lotti and colleagues [31] reported that CESM showed a better correlation with histopathology compared to MRI with Lin's coefficient of 0.81 and 0.59 for CESM and contrast-enhanced MRI, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, we found high sensitivity, specificity, PPV, and NPV of CESM in predicting CR in patients receiving NAC similar to previously published results [2,[30][31][32]. All the forementioned studies, ours included, showed a high sensitivity and a lower specificity of CESM in the assessment of CR which reflects the inability of contrast-enhanced imaging techniques in distinguishing between residual neoplastic disease and associated inflammation and reactive changes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Hence, imaging methods are crucial to predict pathological complete response (pCR) and help monitor clinical response to NAC [4,5]. The most widely accepted imaging techniques are magnetic resonance imaging (MRI) because of its higher sensitivity and specificity to predict pCR [6][7][8], as well as contrastenhanced spectral mammography (CESM) [9][10][11]. Those techniques are more accurate than digital mammography (DM) and US mainly due to intravenous contrast injection that allows a more sensitive imaging analysis in many ways [12,13].…”
Section: Introductionmentioning
confidence: 99%